2013
DOI: 10.4300/jgme-d-12-00117.1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Cost-Conscious Medicine: Impact of a Simple Educational Intervention on Appropriate Abdominal Imaging at a Community-Based Teaching Hospital

Abstract: Background Rising costs pose a major threat to US health care. Residency programs are being asked to teach residents how to provide cost-conscious medical care. Methods An educational intervention incorporating the American College of Radiology appropriateness criteria with lectures on cost-consciousness and on the actual hospital charges for abdominal imaging was implemented for residents at Scripps Mercy Hospital in San Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Numerous studies have found that there is no difference in cost estimation accuracy between HCPs at various levels of training and experience, finding no such differences among medical students, residents, faculty physicians, specialists and physicians. [11,14,15] We found that private practice involvement does not significantly influence cost estimation accuracy.…”
Section: Discussionmentioning
confidence: 71%
“…Numerous studies have found that there is no difference in cost estimation accuracy between HCPs at various levels of training and experience, finding no such differences among medical students, residents, faculty physicians, specialists and physicians. [11,14,15] We found that private practice involvement does not significantly influence cost estimation accuracy.…”
Section: Discussionmentioning
confidence: 71%
“…Another study 20 found that a facile cost-consciousness curriculum could alter resident behavior to reduce unnecessary inpatient imaging. Similar to ours, that educational intervention was based on published guidelines, took the form of didactic lectures targeted at residents, and incorporated reminders.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important observation was that 81 of 126 physicians (64%) still indicated that they consult a radiologist as 1 of their top 3 resources, the most popular choice for both residents and attending physicians. 17 Strother et al 18 incorporated a phased quality improvement initiative designed to educate referring clinicians and departmental radiologists about the recommendations of the ACR AC for dual-phase head CT examinations and demonstrated a reduction in the number of dual-phase head CT examinations that were not indicated. 13 In addition, it has been well documented that educational interventions on the use of imaging testing results in improved utilization.…”
Section: Ac Guidelinesmentioning
confidence: 99%